Nonlinear Shear Waves in Compressible Media: Occurrence of Strong Shocks - Vladimir Bratov; Sergey V. Kuznetsov (Mathematics)
Apparently for the first time, shear shock wave fronts (shear shocks) are observed in a hyperfoam at the propagation of shear waves. The hyperfoam is modelled by the Ogden compressible hyperelastic potential. A possible appearance of the shear shocks may explain the kinetic and strain energy attenuation along with heat release at the propagation of shear waves in hyperfoams. The analysis is based on the Cauchy formalism for equations of motion, equations of energy balance, and FE analysis for solutions of the constructed nonlinear hyperbolic equation.